The Effect of Service Quality, Trust, And Delivery Timelines on Customer Satisfaction at J&T Cargo Kapten Regug - Made Yoga Artika Widyantara; I Gusti Ngurah Agung Gede Eka Teja Kusuma; Made Pradnyan Permana Usadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
The rapid developments of internet technology in Indonesia has significantsly increased e-commerce activities, leading to a growing demand for efficients and reliable logistics and delivery services. J&T Cargo Kapten Regug is one of the expeditions services providers that continues to strive to maintain customers satisfactions amid increasingly intense competitions. However, based on observationss and interviews, several issues were identsified, including unprofessionsal employee performance, customers concerns regarding shipments security, and delivery processes that do not meet estimated timelines. These conditionss motivated this study, which aims to examine the effects of services quality, trust, and delivery timelines on customers satisfactions at J&T Cargo Kapten Regug. This research was conducted at J&T Cargo Kapten Regug. The populations comprised all customers who had used J&T Cargo Kapten Regug’s delivery services, with an unknown total number. A purposive sampling method with a non-probability sampling technique was employed, involving 160 respondents who had previously used the company’s services. Data were collected through observationss, interviews, and the distributions of Likert-scale questionsnaires. The data were analyzed use multiple linear regressionss analysis with the assistance of SPSS versionss 25. The result indicate that services quality, trust, and delivery timelines each have a positive and significants effects on customers satisfactions at J&T Cargo Kapten Regug. These findings suggest that improvements in services quality, increased customers trust, and more timely delivery services contribute significantsly to higher levels of customers satisfactions.